Protein-Based Adjuvants for Vaccines as Immunomodulators of the Innate and Adaptive Immune Response: Current Knowledge, Challenges, and Future Opportunities - Diego A. Díaz-Dinamarca; Michelle L. Salazar; Byron N. Castillo; Augusto Manubens; Abel E. Vasquez; Fabián Salazar; María Inés Becker (MDPI AG, 2022)
New-generation vaccines, formulated with subunits or nucleic acids, are less immunogenic than classical vaccines formulated with live-attenuated or inactivated pathogens. This difference has led to an intensified search for additional potent vaccine adjuvants that meet safety and efficacy criteria and confer long-term protection. This review provides an overview of protein-based adjuvants (PBAs) obtained from different organisms, including bacteria, mollusks, plants, and humans. Notably, despite structural differences, all PBAs show significant immunostimulatory properties, eliciting B-cell- and T-cell-mediated immune responses to administered antigens, providing advantages over many currently adopted adjuvant approaches. Furthermore, PBAs are natural biocompatible and biodegradable substances that induce minimal reactogenicity and toxicity and interact with innate immune receptors, enhancing their endocytosis and modulating subsequent adaptive immune responses. We propose that PBAs can contribute to the development of vaccines against complex pathogens, including intracellular pathogens such as Mycobacterium tuberculosis, those with complex life cycles such as Plasmodium falciparum, those that induce host immune dysfunction such as HIV, those that target immunocompromised individuals such as fungi, those with a latent disease phase such as Herpes, those that are antigenically variable such as SARS-CoV-2 and those that undergo continuous evolution, to reduce the likelihood of outbreaks.